Bismuth sulfide particles, method for producing the same, and use thereof
By adjusting the S/Bi molar ratio and heating process of the bismuth sulfide particles, the problem of insufficient blackness of the existing bismuth sulfide particles is solved, and the effects of high blackness and high infrared reflectivity are achieved.
Patent Information
- Application Number
- CN202080070048.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-10-09
- Filing Date
- 2020-09-30
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2040-09-30
AI Technical Summary
The blackness of existing bismuth sulfide particles is not sufficient and fails to meet the understood blackness standards.
By mixing bismuth compound and sulfur compound in an aqueous dispersion medium, the ratio of the mole number of sulfur atoms to the mole number of bismuth atoms (S/Bi molar ratio) is 3.5 or more and 20 or less, and heating is performed to improve bismuth sulfide. The blackness of the particles.
The high blackness performance of bismuth sulfide particles is achieved. The L* value in the L*a*b* color system is below 22.0, and has high infrared reflectivity and low visible light reflectivity.
Smart Images

Figure CN114502510B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to bismuth sulfide particles, a method for producing the same, and uses thereof, and in particular to an infrared reflective material comprising the bismuth sulfide, a laser reflective material for LiDAR, a solvent composition, a resin composition, a coating composition, and a coating film containing the coating composition. Background Art
[0002] Many existing black pigments use chromium oxides, but during the production process, part of the chromium is converted from trivalent to hexavalent, which may result in a hexavalent chromium-containing pigment. Hexavalent chromium-containing pigments are designated as specified chemical substances and pose safety concerns for humans and the environment.
[0003] Therefore, a technology for using bismuth sulfide, which is not designated as a specific chemical substance, as a black pigment has been studied. For example, Patent Document 1 describes the use of bismuth sulfide particles as a light absorbing material for liquid crystal displays and a black pigment for light-shielding film coatings. The bismuth sulfide particles are obtained by adding an aqueous solution containing 3.3 times the molar number of sodium thiosulfate dissolved in an aqueous solution containing bismuth nitrate pentahydrate and sodium hydroxide to a solution containing bismuth nitrate pentahydrate and sodium hydroxide, and heating the solution while stirring.
[0004] Non-Patent Document 1 describes that black bismuth sulfide particles can be synthesized by adding nitric acid to an aqueous solution containing bismuth nitrate and thiourea in an amount 1.5 times the molar amount of bismuth atoms, followed by hydrothermal synthesis at 180°C.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Laid-Open No. 5-264984
[0008] Non-patent literature
[0009] Non-patent literature 1Materials Letters Vol.63 (2009), pp.1496-1498 Summary of the invention
[0010] Problems to be solved by the invention
[0011] Although bismuth sulfide particles produced by conventional methods are black, the blackness is not sufficient and does not have the blackness that is understood.
[0012] Means of solving the problem
[0013] The inventors conducted intensive research to obtain bismuth sulfide particles with high blackness, and found that in the reaction between bismuth compounds and sulfur compounds, the mixing ratio of these compounds affects the blackness of the bismuth sulfide particles. Based on this, bismuth sulfide particles with higher blackness than before can be obtained, thus completing the present invention.
[0014] That is, the present invention is as follows.
[0015] [1] A bismuth sulfide particle, wherein L * a * b * The L of the powder in the color system * The value is below 22.0.
[0016] [2] The bismuth sulfide particles according to [1], wherein the reflectance at a wavelength of 1200 nm is 30.0% or more.
[0017] [3] The bismuth sulfide particles according to [1] or [2], wherein the reflectance at a wavelength of 750 nm is 15.0% or less.
[0018] [4] The bismuth sulfide particles according to any one of [1] to [3], wherein the reflectance at a wavelength of 1550 nm is 50.0% or more.
[0019] [5] An infrared reflective material comprising the bismuth sulfide particles according to any one of [1] to [4].
[0020] [6] A laser reflective material for LiDAR, comprising the bismuth sulfide particles according to any one of [1] to [4].
[0021] [7] A solvent composition comprising the bismuth sulfide particles according to any one of [1] to [4] and a solvent.
[0022] [8] A resin composition comprising the bismuth sulfide particles according to any one of [1] to [4] and a resin.
[0023] [9] A coating composition comprising the bismuth sulfide particles according to any one of [1] to [4] and a coating resin.
[0024]
[10] A coating film comprising the coating composition according to [9].
[0025]
[11] A method for producing bismuth sulfide particles, comprising the following steps: mixing a bismuth compound and a sulfur compound in an aqueous dispersion medium so that the ratio of the number of moles of sulfur atoms to the number of moles of bismuth atoms (S / Bi molar ratio) is greater than 3.5 and less than 20, and then heating.
[0026] Effects of the Invention
[0027] The bismuth sulfide particles of the present invention have L * a * b * L in the color system * High blackness with a value of 22.0 or less.
[0028] According to the present invention, for example, the following effects can also be achieved.
[0029] The bismuth sulfide particles of the present invention can have a high infrared reflectivity of 30.0% or more at a wavelength of 1200 nm.
[0030] The bismuth sulfide particles of the present invention can be easily produced by mixing specific amounts of a bismuth compound and a sulfur compound in an aqueous dispersion medium and then heating the mixture. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a reflectance spectrum of the bismuth sulfide particle powder of Example 1 of the present invention. DETAILED DESCRIPTION
[0032] The bismuth sulfide particles of the present invention are compounds of bismuth and sulfur represented by the chemical formula Bi(III)2S3, etc. * a * b * The L of the powder in the color system * The value is 22.0 or less, preferably 20.0 or less, more preferably 15.0 or less, and further preferably 10.0 or less. * value, it can be said that the blackness of the bismuth sulfide particles is sufficiently high. * Value, which means CIE 1976Lab (L * a * b * The smaller the value, the lower the lightness. Therefore, for black pigment, L * The smaller the value, the higher the blackness (an index indicating blackness). * The value can be measured by a colorimetric colorimeter or the like, and for example, RM-200QC portable colorimeter (trade name) manufactured by X-rite can be used.
[0033] Also, the so-called "CIE 1976Lab (L * a * b * The "CIELAB color system" is a color space recommended by CIE (International Commission on Illumination) in 1976, also known as CIELAB for short.
[0034] In addition, the bismuth sulfide particles of the present invention are preferably L *a * b * A of powder in color system * The value is -2.0 or more and 5.0 or less, and the b of the powder is preferably * The value is -3.0 or more and 8.0 or less. If it is within this range, the bismuth sulfide particles of the present invention can become black with suppressed red, green, yellow, and blue. * Value, b * Value, which means L * a * b * Index of hue and saturation of the color system, a * The larger the value is on the positive side, the stronger the red is, and the larger the value is on the negative side, the stronger the green is. * The larger the value is on the positive side, the stronger the yellow is, and the larger the value is on the negative side, the stronger the blue is. * Value, b * Value, can be expressed as L * Values are measured in the same way.
[0035] The bismuth sulfide particles of the present invention have the above-mentioned L * The reflectivity of the infrared light is preferably 35.0% or more, and preferably 40.0% or more. The infrared light mentioned here refers to electromagnetic waves with a wavelength of 780nm to 2500nm.
[0036] The reflectivity here refers to the ratio of the reflected light beam to the light beam irradiated to the object. The reflectivity can be measured by a spectrophotometer, for example, the UV / visible / near infrared spectrophotometer V-770 (trade name) manufactured by JASCO Corporation can be used.
[0037] The bismuth sulfide particles of the present invention preferably have a reflectivity of 50.0% or more at a wavelength of 1550 nm, more preferably 60.0% or more, and most preferably 70.0% or more. If the reflectivity is as described above, the particles can be used as laser reflective materials for Laser Imaging Detection and Ranging (LiDAR) at a wavelength of 1550 nm.
[0038] In addition, the bismuth sulfide particles of the present invention preferably have a reflectivity of 15.0% or less at a wavelength of 750 nm, more preferably 13.0% or less, and most preferably 11.0% or less. Within this range, visible light can be fully absorbed, and the blackness of the powder becomes high. The so-called visible light here refers to electromagnetic waves with a wavelength of 380 nm to 780 nm.
[0039] The BET specific surface area value (measured by nitrogen adsorption) of the bismuth sulfide particles of the present invention is preferably 0.1 to 70 m 2 / g(0.1m 2 / g or more and 70m 2 / g or less), more preferably 1 to 40 m 2 / g(1m 2 / g or more and 40m 2 / g or less). More preferably, it is 1.4 to 37 m 2 / g(1.4m 2 / g or more and 37m 2 / g or less). Based on the BET specific surface area value, the average particle size that can be regarded as spherical can be calculated using the following formula 1. The average particle size calculated based on this BET specific surface area value is preferably 0.013 to 8.8 μm (0.013 μm or more and 8.8 μm or less), and more preferably 0.02 to 0.88 μm (0.02 μm or more and 0.88 μm or less). It is further preferably 0.023 to 0.63 μm (0.023 μm or more and 0.63 μm or less).
[0040] Formula 1: L = 6 / (ρ·S)
[0041] Here, L is the average particle size (μm), and ρ is the density of bismuth sulfide (6.78 g / cm 3 ), S is the BET specific surface area of the sample (m 2 / g).
[0042] The bismuth sulfide particles of the present invention can also adjust the pH value of the powder. The so-called powder pH value here refers to the pH value of the aqueous solution after stirring the powder in pure water. The pH value of the aqueous solution can be measured by a pH meter, for example, a pH meter D73 (trade name) manufactured by Horiba, Ltd. can be used. As a method for adjusting the pH value of the powder, for example, leaching treatment with an acid or an alkali can be cited.
[0043] The present invention is a method for producing bismuth sulfide particles, which includes the following steps: mixing a bismuth compound and a sulfur compound in an aqueous dispersion medium so that the ratio of the number of moles of sulfur atoms to the number of moles of bismuth atoms (S / Bi molar ratio) is 3.5 or more and 20 or less, and then heating. In addition, bismuth sulfide particles produced by the method including this step are also one of the modes for implementing the present invention, and the step is a step of mixing a bismuth compound and a sulfur compound in an aqueous dispersion medium so that the ratio of the number of moles of sulfur atoms to the number of moles of bismuth atoms (S / Bi molar ratio) is 3.5 or more and 20 or less, and then heating. The heating temperature is preferably 30° C. or more and 145° C. or less.
[0044] Sulfur compounds, for example, thiocyanates such as potassium thiocyanate and sodium thiocyanate, thiosulfates such as sodium thiosulfate, potassium thiosulfate, and ammonium thiosulfate, or organic sulfur compounds such as thiourea can be used. The sulfur compound can be any of anhydride and hydrate. In addition, the sulfur compound is not limited to the form of powder, and a mixed solution in which the powder is mixed in various solvents (water, formic acid, methanol, ethanol, 1-propanol, 2-propanol, etc.) can also be used. The mixed solution can be in the form of powder remaining in the solvent, or in the form of powder dissolved in the solvent. In addition, known acids and bases can be added to dissolve the powder remaining in the solvent.
[0045] As the bismuth compound, for example, bismuth sulfate, bismuth nitrate, bismuth nitrate pentahydrate, bismuth subnitrate, bismuth hydroxide, bismuth oxide, bismuth chloride, bismuth bromide, bismuth iodide, bismuth oxychloride, bismuth subcarbonate, bismuth basic carbonate, etc. can be used. The bismuth compound is not limited to the form of powder, and can also be a mixed solution in which the powder is mixed in various solvents (water, formic acid, methanol, ethanol, 1-propanol, 2-propanol, etc.).
[0046] In addition, the above-mentioned bismuth compound can also be manufactured by a known method. For example, if it is bismuth hydroxide, it can be manufactured in the following manner. Bismuth nitrate pentahydrate and nitric acid are mixed and heated. Sodium hydroxide is added thereto and ripened to obtain a mixed solution containing bismuth hydroxide. The obtained mixed solution is subjected to solid-liquid separation, and the solid component (bismuth hydroxide) is washed.
[0047] The above-mentioned so-called aqueous dispersion medium is a medium with water as the main component, that is, the content of water is more than 50 mass %. The content of water in the aqueous dispersion medium is preferably more than 80 mass %, more preferably more than 90 mass %, and further preferably 95 mass %. As components other than water, various organic solvents (methanol, ethanol, isopropanol, butanol, acetone, butanone, tetrahydrofuran, etc.) that are dissolved in water can be listed, and it is particularly preferred to contain ethanol. The content of ethanol in the aqueous dispersion medium is preferably less than 10 mass %. By containing an organic solvent, it is possible to manufacture bismuth sulfide with higher blackness.
[0048] The above raw materials may be mixed in any order. That is, the bismuth compound and the aqueous dispersion medium may be mixed in advance and the sulfur compound may be added thereto, or the sulfur compound and the aqueous dispersion medium may be mixed in advance and the bismuth compound may be added thereto. Alternatively, all the raw materials may be added to the aqueous dispersion medium at once and mixed.
[0049] In the raw material mixing step, the sulfur compound and the bismuth compound are mixed so that the S / Bi molar ratio is 3.5 or more and 20 or less. By being in such a range, bismuth sulfide particles with higher blackness can be produced. The S / Bi molar ratio is preferably 5 or more and 12.5 or less, and more preferably 7.5 or more and 10 or less. The S / Bi molar ratio can be calculated by dividing the number of moles of sulfur atoms in the sulfur compound by the number of moles of bismuth atoms in the bismuth compound.
[0050] In the above-mentioned raw material mixing step, additives such as a dispersant, an emulsifier, a thickener, a defoaming agent, a surface conditioner, and an anti-settling agent may be added as necessary.
[0051] The mixed solution obtained by the above-mentioned mixing step preferably has its pH adjusted appropriately according to the raw materials used. For example, when bismuth hydroxide, sodium thiosulfate and water are used as raw materials, the pH of the mixed solution obtained after the mixing step is preferably adjusted to 5 or less. It is more preferred to adjust the pH to 4 or less, and it is further preferred to adjust the pH to 3 or less. The pH adjuster is not particularly limited, and known adjusters such as sulfuric acid, nitric acid, hydrochloric acid, sodium hydroxide, potassium hydroxide, etc. can be used. In addition, sulfuric acid used here is not included in the above-mentioned sulfur compound.
[0052] For mixing the above raw materials, a known mixer such as a stirrer, a mixer, a homogenizer, a blender, etc. can be used.
[0053] Bismuth sulfide particles can be produced by heating the mixed solution obtained by the mixing step. The heating temperature is preferably 30°C or higher, more preferably 30°C or higher and 145°C or lower. By heating at such a temperature, bismuth sulfide with higher blackness can be produced. The heating temperature is more preferably 40°C or higher and 120°C or lower, and further preferably 50°C or higher and 90°C or lower.
[0054] The heating time at the above temperature can be arbitrarily set, but is preferably 0.5 to 10 hours (0.5 hours to 10 hours).
[0055] After the above-mentioned heating process, the mixed solution can also be evaporated and dried as required, or the mixed solution can be separated into solid and liquid. The solid-liquid separation can use a known filtering method, for example, a filter device utilizing pressure filtration such as a rotary press, a filter press, etc. used in industry, or a vacuum filtration device such as a suction filter, a vacuum leaf filter, etc. can usually be used. In addition, centrifugation, etc. can also be used. At this time, it is also possible to clean with pure water, etc. as required.
[0056] In addition, the process of drying the solid component obtained by the above-mentioned solid-liquid separation may also be included. When the drying process is included, the drying temperature and the drying time can be set arbitrarily. For example, the drying temperature is preferably above 30°C and below 120°C, and the drying time is preferably 0.5 to 10 hours (between 0.5 hours and below 10 hours). In the drying process, for example, heating equipment such as a dryer, an oven, and an electric furnace can be used.
[0057] The bismuth sulfide particles produced by the above method can also be appropriately adjusted in particle size using a known pulverizer and classifier.
[0058] The bismuth sulfide particles produced by the above method can be confirmed to be bismuth sulfide by X-ray diffraction method, etc. For example, they can be identified based on the spectrum measured using an X-ray diffractometer Ultima IV (trade name) manufactured by Rigaku Corporation.
[0059] The bismuth sulfide particles of the present invention can also be coated with various inorganic compounds or organic compounds on the particle surface. As inorganic compounds, for example, metal oxides and / or metal hydrated oxides of silicon, aluminum, titanium, zirconium, tin, antimony, etc. can be listed. In addition, as organic compounds, organic compounds such as organosilicon compounds, organometallic compounds, polyol systems, amine systems, and carboxylic acid systems (specifically, trimethylolmethane, trimethylolethane, trimethylolpropane, pentaerythritol, dimethylethanolamine, triethanolamine, stearic acid, oleic acid or their salts, etc.) can be listed. It is also possible to coat the particle surface of bismuth sulfide with the above-mentioned inorganic compound and then coat it with the above-mentioned organic compound. The coating amount of the inorganic compound and the organic compound can be appropriately set.
[0060] As a method for coating the surface of the bismuth sulfide particles with an inorganic compound or an organic compound, an existing surface treatment method such as titanium dioxide pigment can be used. Specifically, it is preferred to add an inorganic compound or an organic compound to a slurry of bismuth sulfide particles and coat them, and it is more preferred to neutralize the inorganic compound and the organic compound in the slurry and precipitate them for coating. In addition, it is also possible to add an inorganic compound or an organic compound to a powder of bismuth sulfide particles and mix them for coating.
[0061] The bismuth sulfide of the present invention may be leached using an acid or an alkali. Examples of the acid used for leaching include inorganic acids such as hydrochloric acid, sulfuric acid, nitric acid, and hydrofluoric acid, and examples of the alkali include sodium hydroxide and potassium hydroxide.
[0062] The bismuth sulfide particles of the present invention can be used as a black pigment by utilizing their pigment properties. In addition, they can also be used as an infrared reflective material by combining their infrared reflective properties. When used as an infrared reflective material, the bismuth sulfide particles of the present invention can also be used in combination with other colorants and infrared reflective agents.
[0063] In addition, the bismuth sulfide particles of the present invention can also be used as laser reflective materials for Laser Imaging Detection and Ranging (LiDAR). In LiDAR, for example, a laser with a wavelength of 1550 nm can be used. Figure 1 The reflectivity of the bismuth sulfide particles of the present invention at a wavelength of 1550 nm is sufficient to be used as a laser reflective material for LiDAR.
[0064] The bismuth sulfide particles of the present invention and the infrared reflective material containing it can be mixed with a solvent to form a dispersion or a suspension (collectively referred to as a solvent composition). As the solvent used for the dispersion or suspension, for example, non-aqueous solvents such as water solvents, alcohols (methanol, butanol, ethylene glycol, etc.), esters (ethyl acetate, etc.), ethers, ketones (acetone, butanone, etc.), aromatic hydrocarbons (toluene, xylene, mineral spirits, etc.), aliphatic hydrocarbons, or their mixed solvents can be listed. In the dispersion or suspension, additives such as dispersants, emulsifiers, antifreeze agents, pH regulators, thickeners, defoamers, etc. can also be contained as needed. The concentration of bismuth sulfide in such a solvent composition can be appropriately set.
[0065] In the mixing process when making the above-mentioned dispersion or suspension, a known mixer can be used. In addition, during the mixing, degassing can also be performed as required. As a mixer, for example, a double-shaft mixer, a three-roller mill, a sand mill, etc. commonly used in industry can be listed. If it is a laboratory scale, a homogenizer or a paint stirrer, etc. can be used. At this time, a pulverizing medium with glass, aluminum oxide, zirconium oxide, zirconium silicate, etc. as a component can also be used as required.
[0066] The bismuth sulfide particles and the infrared reflective material containing the bismuth sulfide particles of the present invention can be mixed with a resin to form a resin composition. Examples of the resin used in the resin composition include the following resins, but are not particularly limited.
[0067] Examples of the thermoplastic resin include:
[0068] (1) General-purpose plastic resins (e.g., (a) polyolefin resins (polyethylene, polypropylene, etc.), (b) polyvinyl chloride resins, (c) acrylonitrile-butadiene-styrene copolymer resins, (d) polystyrene resins, (e) methacrylic acid resins, (f) polyvinylidene chloride, etc.);
[0069] (2) Engineering plastic resins (e.g., (a) polycarbonate resin, (b) polyethylene terephthalate resin, (c) polyamide resin, (d) polyacetal resin, (e) modified polyphenylene ether, (f) fluororesin, etc.);
[0070] (3) Super engineering plastic resins (e.g., (a) polyphenylene sulfide resin (PP), (b) polysulfone resin (PSF), (c) polyethersulfone resin (PES), (d) amorphous polyarylate resin (PAR), (e) liquid crystal polymer (LCP), (f) polyetheretherketone resin (PEEK), (g) polyamideimide (PAI), (h) polyetherimide (PEI), etc.), etc.
[0071] Examples of the thermosetting resin include (a) epoxy resin, (b) phenol resin, (c) unsaturated polyester resin, (d) polyurethane resin, (e) melamine resin, and (f) silicone resin.
[0072] Examples of the thermoplastic elastomer include styrene-based, olefin / alkene-based, vinyl chloride-based, polyurethane-based, and amide-based elastomers.
[0073] In addition, the resin composition may contain various additives such as dispersants, emulsifiers, flame retardants, antifreeze agents, pH adjusters, thickeners, defoamers, ultraviolet absorbers, antioxidants, etc. as needed. The concentration of bismuth sulfide in such a resin composition can be appropriately set, and a high-concentration masterbatch can also be used.
[0074] In the step of mixing with the above-mentioned resin composition, the same method as the mixing step in the preparation of the above-mentioned dispersion or suspension can be used.
[0075] The bismuth sulfide particles of the present invention and the infrared reflective material containing the bismuth sulfide particles can be mixed with a coating resin to form a coating composition. The coating resin is not particularly limited as long as it is generally used for coating applications. For example, various coating resins such as phenolic resin, alkyd resin, acrylic alkyd resin, acrylic resin, acrylic emulsion resin, polyester resin, polyester polyurethane resin, polyether resin, polyolefin resin, polyurethane resin, acrylic polyurethane resin, epoxy resin, modified epoxy resin, silicone resin, acrylic silicone resin, fluororesin, ethylene vinyl acetate copolymer, acrylic-styrene copolymer, amino resin, methacrylic resin, polycarbonate resin, polyvinyl chloride resin, etc. can be used.
[0076] The above-mentioned coating composition may contain various additives, solvents, etc. as needed. As additives, various commonly used dispersants, emulsifiers, antifreeze agents, pH adjusters, thickeners, defoamers, etc. may be cited. As solvents, non-aqueous solvents such as water solvents, alcohols (methanol, butanol, ethylene glycol, etc.), esters (ethyl acetate, etc.), ethers, ketones (acetone, butanone, etc.), aromatic hydrocarbons (toluene, xylene, mineral spirits, etc.), aliphatic hydrocarbons, etc., or mixed solvents thereof may be cited. The concentration of bismuth sulfide in such a coating composition can be appropriately set.
[0077] In the mixing step with the above-mentioned resin, the same method as the mixing step in the preparation of the above-mentioned dispersion or suspension can be used.
[0078] The above dispersion or suspension and the above coating composition can be applied to a substrate and cured to form a coating film. In addition, the coating film can also be used as a black coating film, as an infrared shielding coating film, and more preferably as a heat shielding coating film.
[0079] As a method for applying the above-mentioned dispersion or suspension and the above-mentioned coating composition, general methods such as spin coating, spray coating, roller coating, dip coating, pouring coating, blade coating, electrostatic coating, bar coating, die coating, brush coating, and droplet method can be used without restriction. The tools used for coating the dispersion or suspension and the coating composition can be appropriately selected from known tools such as spray guns, rollers, brushes, bar coaters, and scrapers. If the coating is dried and solidified after coating, a coating film can be obtained. In addition, baking can also be performed after drying. The baking conditions can be appropriately set, for example, it can be baked in an oxidizing atmosphere at a temperature range of more than 40°C and less than 200°C for about 1 to 120 minutes. Under this setting condition, sufficient baking can be performed by the drying furnace of the coil coating line.
[0080] Examples of substrates to which the dispersion or suspension and coating composition is applied include ceramic products, glass products, metal products, plastic products, paper products, and the like.
[0081] The above-mentioned coating film can have the characteristics of a black pigment possessed by the bismuth sulfide of the present invention. * a * b * Color system coating L * The value is 10.0 or less, preferably 7.0 or less.
[0082] Measure the coating L * When the value is set, for example, a coating composition having a pigment mass concentration (PWC) of 29.60% is applied using a doctor bar with a wire rod number of 60 so that the film thickness of the dry coating film reaches 67 μm on a white-black chart paper to form a coating film. The coating film formed on the white ground of the white-black chart paper is measured by a colorimeter. * Value, a * Value, b * As a colorimeter, for example, RM-200QC manufactured by X-rite can be used.
[0083] In addition, the above-mentioned coating film can have the infrared reflection characteristics possessed by the bismuth sulfide particles of the present invention. For example, the solar reflectance of the coating film at a wavelength of 780 to 2500 nm can be made 20.0% or more, preferably 30.0% or more. In addition, since such a coating film can ensure a certain degree of solar reflectance, it can also suppress the temperature rise of the coating film surface compared with general black pigments.
[0084] When measuring the solar reflectance of the coating film at a wavelength of 780 to 2500 nm, for example, a coating composition having a pigment mass concentration (PWC) of 29.60% is prepared and coated on a white-black chart paper using a bar coater with a wire rod number of 60 so that the film thickness of the dry coating film reaches 67 μm to form a coating film. The coating film formed on the white ground of the white-black chart paper is measured for reflectance at a wavelength of 780 to 2500 nm using a spectrophotometer, and the solar reflectance at a wavelength of 780 to 2500 nm can be calculated using the method described in JIS K 5602. As a spectrophotometer, for example, the ultraviolet-visible-near-infrared spectrophotometer V-770 (trade name) manufactured by JASCO Corporation can be used.
[0085] In addition, when measuring the surface temperature of the coating film, for example, a coating composition having a pigment mass concentration (PWC) of 29.60% is prepared and coated on a white-black chart paper using a bar coater with a wire rod number of 60 so that the film thickness of the dry coating film reaches 67 μm to form a coating film. The coating film formed on the white ground of the white-black chart paper is irradiated with infrared rays from above the coating film, and the temperature of the coating film surface after irradiation is measured. For infrared irradiation, for example, an IR-type infrared lamp (trade name) manufactured by Iwasaki Electric Co., Ltd. can be used.
[0086] Furthermore, when the weather resistance of the above-mentioned coating film was evaluated, it was found that the coating film had excellent weather resistance compared with a coating film using a general black pigment.
[0087] The above-mentioned weather resistance can be evaluated based on the time required for the color difference of the coating film before and after the exposure test to reach the specified value. The longer the time required, the better the weather resistance. The exposure test mentioned here is not particularly limited to its method, and an outdoor exposure test or an exposure test using an accelerated weather resistance test device can be used. As an accelerated weather resistance test device, for example, a daylight carbon arc lamp weather resistance tester (sunlight weather resistance test box), a dew point cycle weather resistance tester, an ultraviolet carbon arc lamp weather resistance tester, a xenon arc lamp weather resistance tester, etc. can be listed.
[0088] When calculating the color difference of the coating film, for example, a coating composition having a pigment weight concentration (PWC) of 29.60% is prepared, and the coating composition is applied on a steel plate treated with a primer (zinc phosphate) using a bar coater with a wire rod number of 60 so that the film thickness of the dry coating film is 67 μm to form a coating film to prepare a test piece. The coating film is subjected to an exposure test in a sunlight weathering test chamber, and the coating film after the exposure test is measured using a colorimeter to measure the L * Value, a * Value, b * The color difference is calculated by the method described in JIS K 5600. As a sunlight weathering test chamber, for example, S80 (trade name) manufactured by Suga Test Instruments Co., Ltd. can be used, and as a colorimeter, for example, Spectrocolorimeter SD5000 (trade name) manufactured by Nippon Denshoku Industries Co., Ltd. can be used.
[0089] Example
[0090] Examples of the present invention are shown below, but the present invention is not limited to these examples.
[0091] <L * a * b * Color system powder L * Value, a * Value, b * How to measure the value>
[0092] After the sample was fully pulverized in an agate mortar, the sample was placed in a 20 mm φ aluminum ring, a load of 30 MPa was applied, and pressure molding was performed, and measurement was performed using a portable colorimeter (trade name RM-200QC, manufactured by X-rite).
[0093] <Measurement of reflectivity of powder>
[0094] After the sample was fully crushed in an agate mortar, it was placed in a measuring tank (PSH-002 powder tank manufactured by JASCO Corporation) as a measuring sample. The measuring sample was installed in an integrating sphere unit (ISN-923 manufactured by JASCO Corporation) and the reflectance at a wavelength of 300 to 2500 nm was measured using a UV-visible near-infrared spectrophotometer (trade name V-770 manufactured by JASCO Corporation).
[0095] <Measurement of pH value of powder>
[0096] 1.0 g of a sample was weighed in a 200 mL beaker, 100 mL of pure water was added thereto, and ultrasonic dispersion was performed for 5 minutes. Thereafter, the pH value of the aqueous solution was measured using a pH meter (pH meter D73 (trade name) manufactured by Horiba, Ltd.).
[0097] <Measurement of powder X-ray diffraction spectrum>
[0098] After the sample was fully crushed in an agate mortar, the sample was placed in a measuring tank and measured using a sample horizontal multi-purpose X-ray diffraction device Ultima IV (trade name) manufactured by Rigaku Corporation. The sample was identified by matching the obtained spectrum with the ICSD (Inorganic Crystal Structure Database) provided by the Chemical Information Association. The spectrum was collected under the following measurement conditions.
[0099] (1) Optical system
[0100] (a) Divergence slit 1°
[0101] (b) Scattering slit 1°
[0102] (c) Light receiving slit 0.15 mm
[0103] (d) Monochromatic light receiving slit 0.8 mm
[0104] (2) X-ray
[0105] (a) Wavelength CuKα rays
[0106] (b) The current of the bulb is 50mA
[0107] (c) The voltage of the bulb is 50 kV
[0108] (3) Measurement range: 5~70 degrees.
[0109] (4) Scanning method
[0110] (a) Scanning speed 5° / min
[0111] (b) Step width 0.02deg.
[0112] <Production of bismuth hydroxide>
[0113] 116.8 g of 60% nitric acid (manufactured by Nacalaitesque Co., Ltd.) was added to 277.6 g of pure water, and 146.1 g of bismuth nitrate pentahydrate (manufactured by Kanto Chemical Co., Ltd.) was added thereto and mixed. 1459.5 g of pure water was added to the mixed solution to prepare a bismuth nitrate mixed solution. The bismuth nitrate mixed solution and 3 equivalents of sodium hydroxide aqueous solution were added to 4 L of pure water heated to 70°C while maintaining the pH value at 6.5 to 7.5, and then aged for 10 minutes to obtain a mixed solution containing bismuth hydroxide, which was separated into solid and liquid by suction filtration, washed with pure water, and the bismuth hydroxide was recovered.
[0114] <Production of bismuth sulfide>
[0115] (Example 1)
[0116] Pure water was added to the bismuth hydroxide obtained above to a concentration of 0.08 mol / L, and the mixture was prepared into 3.45 L of slurry. In addition, pure water was added to sodium thiosulfate (manufactured by Nacalaitesque Co., Ltd.) to a concentration of 0.68 mol / L, thereby preparing 1.98 L of a sodium thiosulfate mixed solution. Next, the sodium thiosulfate mixed solution was added to the bismuth hydroxide slurry. The S / Bi molar ratio at this mixed amount was 10. Among them, 150 g of nitric acid diluted to a concentration of 30% was added. The pH value of the mixed solution after the addition of nitric acid was 1.8. The obtained mixed solution was heated to 70°C and stirred for 2 hours, and a black precipitate was obtained in the mixed solution. The black precipitate was recovered by suction filtration, washed with pure water, and dried at 100°C for 3 hours to obtain sample 1 of Example 1. For the obtained sample 1, a was measured. * Value and b * When the value is a * =0.1, b * = -0.4. In addition, the pH value of the powder was 3.2.
[0117] (Example 2)
[0118] Sample 2 was obtained in the same manner as in Example 1 except that the S / Bi molar ratio in Example 1 was changed to 5. For Sample 2, a * Value and b * When the value is a * =0.1, b * =1.2.
[0119] (Example 3)
[0120] Sample 3 was obtained in the same manner as in Example 1 except that the S / Bi molar ratio in Example 1 was changed to 7.5. * Value and b * When the value is a * =0.2, b * =-1.0.
[0121] (Example 4)
[0122] Sample 4 was obtained in the same manner as in Example 1 except that the S / Bi molar ratio in Example 1 was changed to 15. * Value and b * When the value is a * =0.0, b * =2.9.
[0123] (Example 5)
[0124] Sample 5 was obtained in the same manner as in Example 1 except that the heating temperature was changed to 30°C. * Value and b * When the value is a * =1.8, b * =4.2.
[0125] (Example 6)
[0126] Sample 6 was obtained in the same manner as in Example 1 except that the heating temperature was changed to 90°C. * Value and b * When the value is a * =0.2, b * =0.2.
[0127] (Example 7)
[0128] Sample 7 was obtained in the same manner as in Example 1 except that the heating temperature was changed to 120°C. * Value and b * When the value is a * =-0.1, b * =0.8.
[0129] (Example 8)
[0130] Sample 8 was obtained in the same manner as in Example 1 except that bismuth hydroxide in Example 1 was replaced with bismuth nitrate pentahydrate (manufactured by Kanto Chemical Co., Ltd.) and that the pH adjuster added after the raw material mixing step was replaced with sodium hydroxide. The pH value of the aqueous solution after the addition of sodium hydroxide was 4.9. * Value and b * When the value is a * =-0.3, b * =1.5.
[0131] (Example 9)
[0132] After washing the black precipitate obtained in the same manner as in Example 1 with pure water, it was not dried, but pure water was added to the black precipitate in a manner such that the concentration reached 50 g / L, and stirred to form a slurry. The slurry was transferred to a beaker, heated to 70°C, and while fully stirred, sodium aluminate was added to the black precipitate in an amount of 2.0% by mass in terms of Al2O3 for 20 minutes. After addition, 20% by mass sulfuric acid was used to adjust the pH value of the slurry to 7.0. Thereafter, it was stirred for 1 hour. The obtained slurry was filtered, washed, and dried at 100°C for 3 hours to obtain Sample 9 of Example 9.
[0133] (Example 10)
[0134] After washing the black precipitate obtained in the same manner as in Example 1 with pure water, it was not dried, but pure water was added so that the concentration of the black precipitate reached 50 g / L, and stirred to form a slurry. The slurry was transferred to a beaker, and a 3-normal sodium hydroxide aqueous solution was added to adjust the pH value of the slurry to 6.5-7.5. Thereafter, the temperature was raised to 70°C and stirred for 2 hours while maintaining the temperature. The obtained slurry was filtered, washed, and dried at 100°C for 3 hours to obtain Sample 10 of Example 10. The powder pH value of Sample 10 was measured to be 3.9.
[0135] (Comparative Example 1)
[0136] The method was carried out in accordance with Example 1 of Japanese Patent Publication No. 5-264984. 3.33 g of bismuth nitrate pentahydrate and 0.72 g of sodium hydroxide were mixed in 34.3 ml of pure water. In addition, 2.70 g of sodium thiosulfate pentahydrate was mixed in 27.7 ml of pure water. The latter mixture was added to the former mixture, and heated at 95°C for 20 hours while stirring to obtain a precipitate in the mixture. The precipitate was recovered by suction filtration, washed with pure water, and dried at 100°C for 3 hours to obtain sample 11 of Comparative Example 1. The S / Bi molar ratio was 3.3.
[0137] The products of samples 1 to 8 and 11, the L of powder * The values and the reflectance of the powder are shown in Table 1. In addition, the reflectance spectrum of the powder of Sample 1 is shown in Figure 1 middle.
[0138]
Table 1
[0139]
[0140] Samples 1 to 8 were confirmed to be Bi2 S3 by XRD spectra. Sample 11 had a broad peak and could not be identified.
[0141] As shown in Table 1, in the samples (samples 1 to 7) produced with S / Bi molar ratios of 3.5 to 20, the L * On the other hand, if the S / Bi molar ratio is out of the above range, L * A value greater than 22.0 indicates insufficient blackness.
[0142] In addition, in the sample (sample 8) in which the bismuth source as a raw material was changed to bismuth nitrate, it was found that the L * The value is 22.0 or less, which indicates that the blackness is sufficient.
[0143] In addition, samples 1 to 8 all have sufficient blackness, and the reflectivity at a wavelength of 1200nm is 30.0% or more, which shows that they have high infrared reflection characteristics. In addition, the reflectivity at a wavelength of 1550nm is 50.0% or more, which shows that they have high infrared reflection characteristics. In addition, the reflectivity at a wavelength of 750nm is 15.0% or less, which shows that they have low visible light reflectivity.
[0144] <Evaluation of coating properties>
[0145] Using Sample 1, Sample 9 or Sample 10, which fully exhibits the infrared reflection property of black, a coating composition and a coating film were prepared in the following manner, and their L * As a reference example, commercially available carbon black (trade name MA-100: manufactured by Mitsubishi Chemical Corporation) was used.
[0146] <Preparation of coating composition>
[0147] Using sample 1, sample 9 or sample 10, a coating composition was prepared at a pigment mass concentration (PWC) of 29.60%. Specifically, each raw material was put into a 100 ml mayonnaise bottle according to Table 2, and stirred using a stirrer (trade name SM-101: manufactured by (Shanghai) AS-1 Co., Ltd.) to prepare a color paste. Next, 15.6 g of alkyd resin (Alukidir (registered trademark) J-524-IM-60: manufactured by DIC Co., Ltd.) was added to the color paste, and stirred using a stirrer (trade name SM-101: manufactured by (Shanghai) AS-1 Co., Ltd.) to obtain a coating composition.
[0148]
Table 2
[0149]
[0150] <Preparation of coating composition using carbon black (reference example)>
[0151] A coating composition was prepared using commercially available carbon black (trade name MA-100: manufactured by Mitsubishi Chemical Corporation) at a pigment volume concentration (PVC) of 5.8%. Specifically, the raw materials were placed in a 100 ml mayonnaise bottle according to Table 3, and dispersed using a coating conditioner (manufactured by RedDevil) to prepare a color paste. Next, 20.0 g of an alkyd resin (Alukidir (registered trademark) J-524-IM-60: manufactured by DIC Corporation) was added to the color paste, and dispersed using a coating conditioner (manufactured by RedDevil) to obtain a coating composition.
[0152]
Table 3
[0153]
[0154] <Coating film production>
[0155] Sample 1, Sample 9, Sample 10 or a commercially available carbon black coating composition was coated on contrast test paper (JIS qualified product: manufactured by Motofuji) using a bar coater with a wire rod number of 60. After being allowed to stand for 30 minutes, it was dried at 110° C. for 40 minutes using a dryer (trade name DRM-620DA: manufactured by Advan-t) to prepare a coating film with a dry film thickness of 67 μm.
[0156] <L of coating film * Measurement of value>
[0157] The above coating film was measured using a portable colorimeter (trade name RM-200QC: manufactured by X-rite) to measure the L * a * b * L in the color system * Value (L on white ground * value).
[0158] <Measurement of solar reflectance of coating film>
[0159] The above-mentioned coating film was measured for reflectance (reflectance on white ground) at a wavelength of 780 to 2500 nm using a UV-visible near-infrared spectrophotometer V-770 (trade name) manufactured by JASCO Corporation, which was mounted on an integrating sphere unit (trade name ISN-923 manufactured by JASCO Corporation). The measurement data was calculated using the weighting coefficient described in JIS K 5602 to calculate the solar reflectance of the coating film at a wavelength of 780 to 2500 nm.
[0160] L of the coating film using sample 1 * The value is 6.6, and the solar reflectance of the coating film at a wavelength of 780 to 2500 nm is 38.4%.
[0161] L of the coating film using sample 9 * The value is 5.9, and the solar reflectance of the coating film at a wavelength of 780 to 2500 nm is 38.9%.
[0162] L of the coating film using sample 10 * The value is 5.0, and the solar reflectance of the coating film at a wavelength of 780 to 2500 nm is 38.7%.
[0163] Using each coating film of Sample 1, Sample 9 or Sample 10, L * The value is 10.0 or less, which indicates that the blackness is generally required for a black coating film.
[0164] In addition, each coating film using Sample 1, Sample 9, or Sample 10 had a solar reflectance of 20.0% or more, and was found to have infrared reflective properties generally required of infrared reflective coating films.
[0165] The coating film using commercially available carbon black had a solar reflectance of 3.97%, which is smaller than that of the coating film using the bismuth sulfide particles of the present invention. In addition, it was found that the coating film did not have the infrared reflective properties generally required of infrared reflective coating films.
[0166] <Evaluation of coating temperature>
[0167] Using Sample 1 and commercially available carbon black, a coating composition and a coating film were prepared in the above-mentioned manner, and the surface temperature of the coating film after infrared irradiation was measured.
[0168] <Measurement of coating surface temperature>
[0169] A 75 mm square was cut out of the coating film and irradiated with an infrared lamp (IR type infrared lamp (trade name) 250 W manufactured by Iwasaki Electric Co., Ltd.) from a position 400 mm upward from the coating film surface for 20 minutes to measure the coating film surface temperature.
[0170] The surface temperature of the coating film using Sample 1 after infrared irradiation was 59°C.
[0171] The surface temperature of the coating film using commercially available carbon black after infrared irradiation was 78° C., and it was found that the surface temperature of the coating film using the bismuth sulfide of the present invention was lower.
[0172] <Evaluation of weather resistance of coating film>
[0173] Using sample 1 or commercially available carbon black, a coating composition and a coating film were prepared in the above manner, and the weather resistance of the coating film was evaluated. The time required for the color difference of the coating film before and after the exposure test to reach 5 or more was measured.
[0174] <Preparation of test pieces for exposure test>
[0175] Sample 1 or a commercially available carbon black coating composition was applied to a steel plate treated with a primer (zinc phosphate) using a bar coater to a dry film thickness of about 67 μm, and then baked at 110° C. for 40 minutes to prepare a test piece.
[0176] <Calculation of coating color difference before and after exposure test>
[0177] The test pieces were exposed to light using a sunlight weathering test chamber (SuGa Tester Co., Ltd., trade name S80) and water was sprayed at regular intervals for accelerated exposure. Color was measured at regular intervals using a colorimeter (Spectrophotometer, trade name SD5000, manufactured by Nippon Denshoku Industries Co., Ltd.), and the color difference was calculated by a method conforming to JIS K 5600.
[0178] In the coating film of Sample 1, it took 600 hours for the color difference between before and after the exposure test to reach 5 or more, which shows that the weather resistance is good.
[0179] For a coating film using commercially available carbon black, it took 180 hours for the color difference before and after the exposure test to reach 5 or more.
[0180] Industrial Applicability
[0181] The bismuth sulfide particles of the present invention have L * a * b * L in the color system * The bismuth sulfide particles of the present invention have a high blackness of 22.0 or less, and are therefore useful as black pigments. Furthermore, the bismuth sulfide particles of the present invention have a high infrared reflectivity of 30.0% or more at a wavelength of 1200 nm, and are therefore useful as infrared reflective materials.
Claims
1. A bismuth sulfide particle, wherein: L * a * b * The L of the powder in the color system * The value is below 22.
0.
2. The bismuth sulfide particles according to claim 1, wherein The reflectivity at a wavelength of 1200 nm is 30.0% or more.
3. The bismuth sulfide particles according to claim 1 or 2, wherein The reflectivity at a wavelength of 750 nm is 15.0% or less.
4. The bismuth sulfide particles according to claim 1 or 2, wherein The reflectivity at a wavelength of 1550 nm is 50.0% or more.
5. An infrared reflective material, wherein: Containing the bismuth sulfide particles according to any one of claims 1 to 4.
6. A laser reflective material for LiDAR, wherein: Containing the bismuth sulfide particles according to any one of claims 1 to 4.
7. A solvent composition, wherein Contains the bismuth sulfide particles according to any one of claims 1 to 4 and a solvent.
8. A resin composition, wherein The method comprises the bismuth sulfide particles according to any one of claims 1 to 4 and a resin.
9. A coating composition, wherein: The invention comprises the bismuth sulfide particles according to any one of claims 1 to 4 and a coating resin.
10. A coating film, wherein A coating composition comprising the coating composition according to claim 9.
11. A method for producing bismuth sulfide particles, wherein: Including the following processes: A mixing step of mixing a bismuth compound and a sulfur compound in an aqueous dispersion medium so that the ratio of the number of moles of sulfur atoms to the number of moles of bismuth atoms (S / Bi) is 3.5 or more and 20 or less to obtain a mixed solution of a slurry of the bismuth compound and the sulfur compound; Next, a step of adding a pH adjuster to the mixed solution; Next, the pH-adjusted mixed solution is heated at 30°C to 120°C. The aqueous dispersion medium is water, or contains water as a main component and 10% by mass or less of an organic solvent.
Citation Information
Patent Citations
Light-absorbing materials for liquid crystal displays, light shielding films and liquid crystal display panels
JP1993264984A
Bismuth sulfide electrode material with specific morphologic structure and application thereof
CN106299357A
Water-phase preparation method of near-infrared photothermal nanomaterial bismuth sulfide
CN107098387A